2013
DOI: 10.1111/imm.12079
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates immune‐complex‐mediated glomerulonephritis in factor‐H‐deficient mice

Abstract: SummaryComplement factor H (Cfh) is a key regulator of the complement cascade and protects C57BL/6 mice from immune complex-mediated complement-dependent glomerulonephritis. In chronic serum sickness (CSS) there are increased deposits of immune complexes in the glomeruli with inflammation and a scarring phenotype. As cucurmin is an effective antiinflammatory agent and reduces complement activation, we hypothesized that it should alleviate renal disease in this setting. To determine the effectiveness of curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 57 publications
4
28
0
1
Order By: Relevance
“…Curcumin is reported to reduce glomerulosclerosis, improve kidney function in factor‐H‐deficient mice , ameliorate macrophage infiltration in renal glomeruli of streptozotocin‐induced diabetic rats , and decrease proteinuria in New Zealand Black/White mice and glomerulonephritic animals . In our previous study, curcumin and pioglitazone inhibited PTP1B and increased p‐IR and p‐IRS‐1 to enhance Akt and ERK1/2 activation in the liver of fructose‐fed rats .…”
Section: Discussionmentioning
confidence: 84%
“…Curcumin is reported to reduce glomerulosclerosis, improve kidney function in factor‐H‐deficient mice , ameliorate macrophage infiltration in renal glomeruli of streptozotocin‐induced diabetic rats , and decrease proteinuria in New Zealand Black/White mice and glomerulonephritic animals . In our previous study, curcumin and pioglitazone inhibited PTP1B and increased p‐IR and p‐IRS‐1 to enhance Akt and ERK1/2 activation in the liver of fructose‐fed rats .…”
Section: Discussionmentioning
confidence: 84%
“…Curcumin significantly attenuated the reduction of serum GPx and the levels of urea, cystatin C, and MDA in serum and the increase of the MDA concentration, nitric oxide and protein carbonyl content in kidney of rats with I/R [15]. On the other hand, Jacob et al [41] observed, in mice with deficient immune response and glomerulonephritis injury, that curcumin administration reduces GS and improves renal function (evaluated by BUN and albuminuria), which was associated to a decrease in inflammatory markers (TGF-β and MCP-1) and matrix proteins (fibronectin, laminin and collagen).…”
Section: Renoprotective Effect Of Curcuminmentioning
confidence: 92%
“…Our studies showing significantly increased oxidative damage in lupus patients [19][20][21] led us to investigate an antioxidant/anti-inflammatory agent known as curcumin, [22][23][24][25][26][27][28][29][30][31] obtained from the rhizome of Curcuma longa (turmeric). Curcumin (1,7-bis[4-hydroxy-3-methoxyphenyl]-1,6-heptadiene-3,5-dione), a naturally occurring 'nutraceutical', comprises 4-6% of turmeric.…”
Section: Ultrasoluble Curcuminmentioning
confidence: 99%